(untitled) (Comprehensive Journal of Science, 2025)
Soft white cheese is a very popular traditional dairy product in Libya and is made from fresh or pasteurized milk. There are currently few documented reports on the production of fresh Libyan white cheese using Lactic acid bacteria. Thus, this study proposed a new protocol for producing soft white cheese using a mixture of whole cow’s milk and whole milk powder, with the addition of lactic acid bacteria strains to obtain a probiotic-enriched cheese and reduce the proportion of whey as a by-product. Different ratios of whole milk powder (0, 10, 20, and 30%) were added to whole cow’s milk during cheese production. The results showed that cheese yield increased to 74.43% when 30% milk powder was used, compared to 12.23, 26.70, and 55.10% for cheeses made with 0, 10, and 20% milk powder, respectively. Sensory evaluation revealed that using 10–20% milk powder combined with lactic acid bacteria starter had no significant effect on the sensory properties of the soft cheese compared to traditional white cheese. However, excessive addition of milk powder reduced sensory acceptance among panelists. To improve yield and texture quality without negatively affecting sensory characteristics, a balanced combination of the two milk sources is recommended to produce a high-quality product that meets consumer preferences.